Brand Awareness, Ad Attıtudes and Ad Features Toward Engagement on Youtube: an Empırıcal Study of Green Automobıles - Ayu Febriyanti Puspitasari; Chien Wen Shen (APMBA (Asia Pacific Management and Business Application), 2014)
The purpose of this paper is to develop suitable measurements for brand awareness, ad attitudes, ad features, and customer engagement on YouTube, also to investigate the relationships among brand awareness, ad attitudes, ad features toward engagements on YouTube and conduct an empirical study of green automobile videos on YouTube channel. YouTube as social media video sharing platform are used as a platform to investigate customer engagements. The study utilizes statistics data from YouTube channel. There are 7 green car model of video advertisements chosen as the sample of this study. Total number of observations are 633 green car video advertisements on YouTube. Comparison of full model and reduced model also multiple linear regression are conducted to analyze the relationship among brand awareness, ad attitudes, ad features toward engagements. The result shows thatbrand awareness and ad attitudes play very important role to engage customer on YouTube. Hence ad features doesn’t significantly play important role to engage customer on YouTube. The result of this research also shows that green or non-green messages which delivered by each video advertisement is not influence significantly. Indicate that it is important for company to consider use YouTube as one of video sharing platform to engage their customer through online video advertisements.This research model also can be used for another social media in example facebook, twitter, etc with different measurement. This research framework also can be used to analyze the effectiveness of company’s engagement process on YouTube. Online advertisers therefore should work with companies that operate social media websites especially use YouTube to increase the persuasive effects of interactivity, make advertised products more tangible for potential consumers, identify the most important attributes, and use these attributes in advertising. There is no previous research addresses about this kind of issues. The study combine three variables brand awareness, ad attitudes, and ad features toward engagement together and focus on YouTube as video sharing platform.